(untitled) (ARQUISUR Revista, 2021)
Based on the sustainable development objectives of Agenda 2030, it is understood the importance of seeking solutions that help mitigate the problems of food security that have intensified with the pandemic of COVID-19, through the most appropriate design of our cities. Thus, the requalification of urban centers is proposed as a measure for sustainable urban development, since it imposes the challenge of remaking the existing city, reinventing it, in an intelligent and inclusive way. In this sense, urban gardens can occupy urban voids and block quarters of consolidated urban centers. Urban gardens have been identified as important multipurpose spaces, not only to produce food, but also to provide leisure spaces, essential for cities that seek sustainability and responsiveness to the needs of local inhabitants. In conclusion, this article intends to provide subsidies for projects of requalification of urban centers, suggesting the strategy of including urban gardens in urban voids and block brains to be replicated, considering all their possible benefits, to improve the quality of life in urban centers and contribute to the production of sustainable and healthy cities.